2020
DOI: 10.21203/rs.2.23064/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

β-glucosidase genes differentially expressed during composting

Abstract: Background: Cellulose degradation by cellulase is brought about by complex communities of interacting microorganism, which significantly to the cycling of carbon on a global scale. β-Glucosidase is the rate-limiting enzyme of degradation of cellulose. Thus, analysis of expression of genes involved in cellulose degradation and regulation of β-glucosidase gene expression in composting is beneficial to a better understanding of cellulose degradation mechanism. According to our previous researches, we present the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…These results indicated that under the general condition that no CCR effect occurs during cellulose degradation, the functional microbial communities mainly expressed non-glucose tolerant β-glucosidase participate in the process of cellulose degradation. This result was consistent with Zhang [ 7 ] and Mathew [ 53 ], which is a prevalent economic microbial behavior. Meanwhile, the ratio of glucose-tolerant β-glucosidase genes in all treatments at T2 phase was lower than that at the T1 phase in the DNA library (Additional file 2 : Table S2), indicating that the non-glucose β-glucosidase genes are the main components of β-glucosidase genes at T2 phase.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…These results indicated that under the general condition that no CCR effect occurs during cellulose degradation, the functional microbial communities mainly expressed non-glucose tolerant β-glucosidase participate in the process of cellulose degradation. This result was consistent with Zhang [ 7 ] and Mathew [ 53 ], which is a prevalent economic microbial behavior. Meanwhile, the ratio of glucose-tolerant β-glucosidase genes in all treatments at T2 phase was lower than that at the T1 phase in the DNA library (Additional file 2 : Table S2), indicating that the non-glucose β-glucosidase genes are the main components of β-glucosidase genes at T2 phase.…”
Section: Discussionsupporting
confidence: 92%
“…In G H C H treatment, the microbial community composition shifted; the abundance of Firmicutes increased, while Actinobacteria decreased. Considering that community structure is closely related to the function of microbial communities [ 7 ]. Actinobacteria were known to play an important role in decomposing organic materials in composts [ 34 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations